Blood AST and ALT profile of Sumba Ongole cattle - Cynthia Dewi Gaina; Maxs U.E. Sanam; Wilmientje M.M. Nalley; Imanuel Benu; Agus Saputra (ARSHI Veterinary Letters, 2020)
A study was carried out in one of Indonesia native cattle, Sumba Ongole (SO) Cattle for determination of statuses of various biochemical parameters, aspartate aminotransferase (AST or SGOT) and alanine aminotransferase (ALT or SGPT). Apparently blood from randomly selected cattle (n= 36) were collected aseptically. Biochemical analysis of AST and ALT was performed on UPT. Laboratorium Kesehatan, Kupang, NTT. The results showed that the variations of parameters were not significant (p>0.05) between male and female SO cattle. The AST/SGOT (142.56±20.55 U/l) was slightly higher in female compared with the male (137.00±16.24 U/l), while level of ALT/SGPT were 46.44±10.99 U/l in male and 46.41 ± 10.23 U/l in female. Although, the result was not significant (p>0.05), level of AST and ALT in SO cattle was higher compared to standard which is 60-125 U/l for AST and 6.9-35 U/l for ALT. Results showed possibility of seasonal effect on AST/ SGOT and ALT/SGPT level in male and female SO cattle.